Slow Culture and Fast Culture: Challenges of Upbringing for the Contemporary Family - Maciaszek, Paweł (Paedagogia Christiana, 2026)
The text presents two contrasting cultures that are relevant to the family’s educational tasks. In the first two parts of the study, slow culture and fast culture are described. Their creators and assumptions are presented, as well as their influence on such everyday activities as preparing and eating meals, doing professional work and housework, organising leisure time and rest, reflecting on the meaning of life and the way of living it, building relationships with people, searching for joy and happiness. The content of the first two parts of the article is used in the third one; it presents the importance of the individual elements of both cultures for the upbringing process taking place in the family. On the one hand (in fast culture) there is the constant rush and lack of time, the pursuit of being better than others and achieving professional success, taking on more and more responsibilities in order to multiply material goods and the associated consumerism, the use of new developments in the field of technology and globalisation encompassing all spheres of life. On the other hand (in slow culture) there is finding the right pace of life for people, constant readiness to help, caring for relationships, nurturing traditional values. It was pointed out which of these elements should be used in the shaping of young generations and which may pose a threat to the modern family.